Igreja e Eucaristia, festa e sacrifício - Cipolini, Pedro Carlos (Revista Eclesiástica Brasileira, 2006)
O artigo reflete sobre a íntima relação que vigora entre a Igreja e a Eucaristia: a Eucaristia une o povo fiel, faz o povo de Deus participar na vitória de Cristo, bem como o introduz na dimensão do Reino de Deus. Explora também o rico simbolismo do pão e do vinho, de origem bíblica, e aprofunda o sentido destas duas dimensões do mistério pascal celebrado na Eucaristia: refeição/convívio e sacrifício/entrega. Recorda a necessidade de um justo equilíbrio entre as dimensões de festa e sacrifício do mistério eucarístico. Mostra, por fim, que a participação na Eucaristia torna os fiéis missionários da Boa-Nova do Reino de fraternidade e paz, anunciadores de um mundo novo e liberto, criado pela “fração do pão”, e da vitória do “Ressuscitado”, penhor de nossa ressurreição, a festa que não tem fim. Abstract: The article deals with the close relation that prevails between the Church and the Eucharist: the Eucharist brings together the faithful, encourages God’s people to participate in Christ’s victory and introduces them into the dimension of God’s Kingdom. It also explores the rich symbolism of the bread and wine, originated in the Bible, and strengthens the meaning of these two dimensions of the paschal mystery celebrated in the Eucharist: meals/convivial spirit and sacrifice/surrender. It reminds us of the need for a fair balance between the dimensions of festivity and sacrifice in the Eucharistic mystery. Finally its shows that participation in the Eucharist turns the faithful into missionaries of the Good Tidings of the Kingdom i. e. the fraternity and peace that herald a new, free world, created by the “fraction of the bread” and the victory of “the one who resurrected”, the pledge of our resurrection, the endless feast.